Perspectives for development social entrepreneurship in republic of Moldova - Stratan, Dumitru (Applied Studies in Agribusiness and Commerce, 2016)
Social entrepreneurship, as a field for research and scientific disputes between scholars and practitioners, it still remains a novel investigation area, as far as new opportunities, challenges, business approaches and concepts appear into the modern world and competitive market. This paper puts emphasis on social framework behind the development of social businesses in Moldova. Moreover, it presents the grass-root state of readiness of existing small and medium – sized enterprises from Moldova to undertake the leap towards the new kind of economy and different organizational approaches. The paper provides a content analysis of specific literature on social entrepreneurship, with particular emphasis on general perception of the small holders and small and medium – sized enterprises on social business. A total number of 593 small and medium – sized enterprises and individuals participated to organized interviews. The survey results show that 66% of the respondents are not acknowledged with social entrepreneurship concept and functionality. From those (34%) who are informed about the topic, most of them are actual young entrepreneurs. Additionally, young entrepreneurs, respondents, wouldn’t reinvest their profit for social mission (73%). Unlike young entrepreneurs, individuals would reinvest their profit in social missions, in case they have a business. These findings suggest that, in the society there is a lack of general understanding on social entrepreneurship. The author also found out that, the general perception regarding social problems is mostly assigned to public authorities instead of enterprises. Moreover, the research results show that the absence of a clear mechanism which would raise public awareness regarding social problems and social capital, affects the active implication of community stakeholders into the societal problems.JEL code: M140